Risk factors for venous thromboembolism in Slovenian children and adolescents: a single center experience - Leban, Mineja; Kavčič, Marko; Peterlin, Jakob; Jazbec, Janez; Faganel Kotnik, Barbara (Frontiers in Pediatrics, 2026)
Venous thromboembolism (VTE) are rare but potentially life-threatening conditions in children, usually associated with underlying medical conditions. Some children with diagnosed VTE have genetic risk factors for the development of VTE, as well as for recurrent complications. This study reports risk factors for developing VTE in a homogeneous population of children and adolescents. A total of 155 children and adolescents, aged 0–21 years, who were diagnosed with VTE at the University Children's Hospital, UMC Ljubljana, between July 2006 and October 2021, were included. The median age at the time of the VTE diagnosis was 12.0 years (interquartile range: 1–7 years). Associated medical conditions were present in 75.5% of patients, and thrombophilia was diagnosed in 43.2% of patients. Oncological disease accounted for 27.7% of cases, while infections were found to be the most significant acquired risk factor (17.4%), followed by the presence of a central venous catheter (15.5%). Genetic thrombophilia markers were identified in 27.1% of patients, with the highest frequency in adolescents (62.5%). Factor V (FV) Leiden heterozygote was the most common marker (9.6% of patients), followed by elevated factor VIII (FVIII) activity (5.8%) and elevated Lp(a) levels (5.2%). Combined thrombophilia markers were found in 52.2% of patients. In addition to inherited thrombophilia, 83.3% of patients had acquired risk factors. Compared to previously reported prevalence, a lower occurrence of FV Leiden heterozygote, elevated Lp(a) levels, elevated FVIII activity and antiphospholipid syndrome was observed in our population.